Evaluation Of The Implementation Of An Integrated Esg Strategy In Support Of Achieving Gold Proper In 2024: A Case Study Of The Implementation By PT. Adaro Energy Indonesia - Dika Fuji Okta; Carmel Meiden (Return : Study of Management, Economic and Bussines, 2025)
Abstract: PT. Adaro Energy Indonesia Tbk. has officially changed its name to PT. Alamtri Resource Indonesia Tbk., one of the largest coal mining companies in Indonesia, demonstrating its strong commitment to sustainable business practices in the coal sector. The name change is not merely about rebranding but also reflects the company's expanded role in environmental, social, and governance (ESG) aspects, which are now fully integrated into its operational strategy. PT. Adaro Energy Indonesia Tbk. has demonstrated its success by receiving the PROPER Gold Award from the Ministry of Environment and Forestry (KLHK) consecutively from 2020 to 2024, which serves as tangible evidence that the company not only complies with environmental regulations but also implements practices that exceed previously established standards (beyond compliance). This study uses a mixed-method approach that combines quantitative and qualitative methods to explore the implementation of ESG at PT. Adaro Energy Indonesia Tbk. The result of this research is PT. Adaro Energy Indonesia Tbk in its process of achieving the PROPER Gold award from 2020 to 2024, where it is known that the award is given by the Ministry of Environment and Forestry (KLHK) to recognize companies for their performance evaluations, which include environmental management that not only complies with existing regulations but also encourages companies to continue innovating in environmental and social aspects. Thus, ESG is not only a compliance instrument, but has been internalized as a strategic framework and value in building the company's reputation and legitimacy amid the dynamics of ongoing demands..